Optimization of high performance liquid chromatography and PCR for determination of aflatoxin and ochratoxin a in peanuts - Afsah Hejri, Leili (2012)
Aflatoxins (AFs) are carcinogenic, mutagenic, and hepatotoxic compounds, and ochratoxin A (OTA) is a possible carcinogen to humans. Malaysia is a tropical country favoring the growth of aflatoxin and ochratoxin producer strains. To reduce the health risk from the consumption of aflatoxin and ochratoxincontaminated food, accurate and effective detection methods are highly needed. This research was conducted to optimize a reversed phase high performance liquid chromatography fluorescence detection method for the determination of AFs and OTA and to isolate potential aflatoxin and ochratoxin producer strains from raw peanuts marketed in Malaysia. Moreover, aflatoxin and ochratoxinproducer strains were also detected using polymerase chain reaction analysis. The effect of high performance liquid chromatography (HPLC) conditions, including mobile phase composition, temperature and flow rate, on the peak areas of four target AFs (aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2)) from spiked peanuts was investigated using response surface methodology (RSM). The highest quantification value for target AFs was obtained with the following HPLC conditions: mobile phase composition of ACN/H2O/MeOH (8:54:38), temperature of 24ºC and flow rate of 0.4 mL/min. The limits of detection (LOD) values were 0.03, 0.01, 0.09 and 0.06 ng/mL for AFB1, AFB2, AFG1 and AFG2, respectively. The recovery values for AFB1, AFB2, AFG1 and AFG2, were 91.57, 89.37, 89.42 and 76.14 %, respectively. The recommended optimal HPLC conditions provided peak areas for all target AFs by 1 to 2.5-fold higher than two other conditions that are generally used for aflatoxin detection. The level of AFB1 contamination in six brands of raw peanuts ranged from 0.45 to 977.16 ng/g. A significant nonlinear response surface model was fitted to evaluate the effect of HPLC parameters (pH, temperature and flow rate) on the quantification level of OTA. All the HPLC variables had a significant (p < 0.05) effect on the quantification level of OTA. The highest quantification value for OTA was obtained with the following HPLC conditions: mobile phase consisting of 5 mM sodium acetate (pH 2.36)/ACN/MeOH (40:30:30), excitation of 333 nm, emission of 467 nm, temperature of 24°C, and flow rate of 0.4 mL/min. The recommended optimal HPLC conditions provided a 2.2-fold to 4.7-fold higher peak area for OTA when compared to two other routinely used HPLC conditions. The recovery and LOD values of OTA under the recommended optimal conditions were 95.4% and 0.05 ng/g, respectively. The OTA contents of the analyzed peanut samples ranged from 2.82 to 7.41 ng/g. Sixty raw peanut samples were used for fungal isolation. Based on the results of the morphological studies, Aspergillus species were isolated from the peanut samples. A total of 23 Aspergillus (black and green aspergilli) isolates were obtained from the samples. Production of AFB1 and OTA by the isolates in culture media was analyzed using the optimized HPLC methods. Three-day-old purified green Aspergillus isolates grown at 30ºC on potato dextrose agar (PDA) plates were screened for their aflatoxin-producing ability using ammonia vapor. The pink/red color of colony reverse represented aflatoxin-producing strains. The results of the screening test were in agreement with the HPLC results of toxin production in media. To detect aflatoxigenic and ochratoxigenic isolates, specific primers targeting the genes responsible for aflatoxin and ochratoxin production were used. Three primer sets were used for the detection of aflatoxigenic isolates, and three primer sets were used for the detection of ochratoxigenic isolates. The results of the PCR amplification were in agreement with the HPLC chromatogram of AFB1 and OTA production of isolates. A total of 14 aflatoxigenic, 5 ochratoxigenic and 4 non-aflatoxigenic/non-ochratoxigenic Aspergillus were isolated from raw peanuts marketed in Malaysia.